Os desafios do ensino superior policial-militar no Brasil : um estudo de caso sobre currículos de cursos de graduação em ciências policiais - Martins, Isabel Cristina dos Santos (2022)
Military education in Brazil is developed by educational institutions that operate at the federal level: Armed Forces (Aeronautics, Navy and Land/Army) and state: Auxiliary Forces (Military Police of the 27 federative entities). The inclusion of police science in the list of sciences studied in Brazil, Opinion CNE/CES nº 945/2019, approved in 2020, established a watershed for the studies and training carried out until then, in the Military Police of Brazil. The Officer Training Course (CFO) is a tradition of professional training carried out in institutions, for entry to the first post of the Officer's career. At the Military Police of the Federal District, the name of the course was changed in 2013, when the ISCP was accredited in the national education system, in order to give the trained officer also the title of Bachelor of Police Science. When considering that other changes may also have occurred in the other Military Police of Brazil, in relation to the accreditation of new Institutions of Higher Education Police-Military (IES PM) in the national education system and, mainly, the creation of undergraduate courses in police sciences, it became important to identify these institutions, to know the curriculum of the courses and to highlight the innovations that they bring to the process of training public security professionals, motivating the construction of the central question of this research, which sought to understand: what conceptions and practices are explained in the curricula of police science officer training courses? In this context, the general objective of this study is: to evaluate the theoretical and methodological assumptions that organize the curricula of undergraduate courses in police science, of Police-Military Higher Education Institutions accredited in the national education system. The Theoretical Framework was formed with approaches to: 1) police-military higher education, its trajectory, challenges around the concepts of police and police science and national guidelines for professional training; 2) the higher education system, the rules for evaluating undergraduate courses and the role of the curriculum at this level of education; and 3) a review of the literature on police-military higher education and police science in Brazil.The Methodological Assumptions outlined the research as a multiple case study (YIN, 2015), with a qualitative approach (BOGDAN; BIKLEN, 1994; YIN, 2016), with exploratorydescriptive objectives (DOOLEY, 2002; YIN, 2015) and mixed method (YIN, 2015; GIL, 2008): deductive in the logic of construction of the thesis report and inductive in the development of data analysis. The Systematic Review of Literature-RSL (GALVÃO; RICARTE, 2019; RAMOS, FARIA; FARIA, 2014, OKOLI, 2019; CAIADO et al., 2016), carried out from 2001 to 2020, gathered the identification data of the institutions and policemilitary education courses accredited in the national education system, the rules that regulate accreditation and authorization of these courses, the scientific production on police-military higher education and police sciences. From the data collected in the RSL, there was the selection of three more Military Police: São Paulo, Espírito Santo and Santa Catarina, whose training courses of officers are also in the area of police sciences, which contributed to the characterization of the research in a multiple case study involving PMSC, PMDF, PMES and PMESP, as well as to the delimitation of the investigation, enabling the production of analysis on the Political Pedagogical Projects of the Courses, through the Analysis Method Discursive Textual-ATD (MORAES; GALIAZZI, 2011). As an integral part of the literature review, the ATD allowed us to establish a more detailed look at the theoretical-methodological assumptions chosen for the courses, and to conclude that the prescribed (formal) curriculum, planned by the IES PM, presents, in general terms, a sequence (path) sustainable, composed of essential elements, which are interrelated with equity, within the logic of interpretation assessed with the ATD, to give effectiveness to the training intended by the institutions. Therefore, the curricula cannot be classified as traditional, as they are aligned with pedagogical concepts and areas of knowledge, guided by general national guidelines (BRASIL, 2014a; BRASIL, 2019) and arising from the academic-professional experiences acquired by the IES PM, during the time of accreditation in the national education system. In this context, more than professionals in the area of public security, the courses aim to train citizens and “police scientists”, who are able to interpret social events, improve academically and professionally, and apply the set of knowledge and experiences acquired in the systematic and methodical development of this science, with a view to contributing to the fulfillment of the social function of the Military Police, within the scope of Public Security. It is hoped that carrying out this investigation can contribute to the minimization of gaps that perpetuate ignorance, allow the mistaken dissemination of information and hinder the advancement of studies, discussions, reflections and networking, in favor of the qualification of police-military and the provision of services by these agents to society.